Classification of face images using discrete cosine transform - Karhan, Zehra; Ergen, Burhan (My University, 2013)
In this study, it is aimed to determine whether a given image belongs to fort hat person. For feature extraction ,which is an important part of pattern recognition, feature vector is obtained by using discrete cosine transform after performing preprocess the images on the current face. Based on the of datas obtained from conversion are classified by using 5%, 8%, 10%, and 15%. The nearest neighbor algorithm (KNN) is used in classification process.Face images consist of images that, taken from ORL database, belongs to 40 individuals, each has 10 different images. As a result, high success were obtained by using the few data. © 2013 IEEE.
Yüz imgelerinin ayrik kosinüs dönüsümü yardimiyla siniflandirilmas
2013 21st Signal Processing and Communications Applications Conference, SIU 2013 -- 24 April 2013 through 26 April 2013 -- Haspolat -- 98109
Keywords: Discrete cosinüs transform; K NN classifier; Pattern recognition